The Typewritten Archives of Cornell Woolrich. (March 2023) - King, Rob
Abstract : This paper offers a media-archaeological inquiry into Cornell Woolrich's fiction by looking at the media technology from which it sprang: his typewriter. In his 1986 study, Gramophone, Film, Typewriter, media theorist Friedrich Kittler identified the innovative characteristics of the typewriter with a shift from the handwritten word as flowing image to the typewritten word as disembodied and anonymised. This paper uses the case study of Cornell Woolrich to build upon and qualify these observations. It shows how Woolrich's typewriter worked to decenter the notion of an authorial self, opening instead onto possibilities for pseudonymity and anonymity that would inform both his crime fiction and his own life. These themes are then explored through three Woolrich short stories in which typewriters play a prominent role – 'Murder Story', 'The Girl Next Door' (both 1937), and 'The Penny-a-Worder' (1958) – in each of which the typewriter becomes a vehicle for fears and fantasies about the relations between words and their authors. Finally, the paper explores how Woolrich's work exemplifies the typewriter as a writing technology governed by a dialectic of presence and absence, in contradistinction to the pervasive virtualization of digital word processing.